The Main Phonetic and Morphological Features in the Deep Tamian (Tāmnieki) Subdialects of the Livonianized Dialect Nowadays - Vēvere, Daira (Acta humanitarica academiae Saulensis, 2019)
The present research aims at showing the usage of the most characteristic dialectal features in the deep Tamian subdialects of the Livonianized dialect nowadays. Main focus is on the typical phonetic and morphological features and the sociolinguistic observations of these subdialects. Analysis is based on the middle and older generation’s speech data gathered by recording the subdialects of Pope, Ziras, Piltene, Zlēkas, Ance, Dundaga, and Ugāle. The data analyzed in this paper gathered in the expeditions carried out by the author (2008–2017).In the majority of the researched deep Tamian subdialects the loss of short vowels and the reduction of long vowels in final syllables is still observed. Although these are the most typical phonetic peculiarities of the entire Livonianized dialect and are used by all generations’ speakers, those also tend to change even in the deep subdialects of Kurzeme not only in the speech of the younger generation’s speech, but also middle and older generation’s speakers begin to avoid using those, preferring standard language forms. Nowadays there are also several features in the deep Tamian subdialects which are used in the speech of the older generation only and which change under the influence of the standard language, for example, the loss of long vowels and diphthongs in suffixes and endings, the monophthongization and diphthongization, and other phonetic changes which are specific to the deep Tamian subdialects.One of the most prominent morphological features of the deep Tamian subdialects is the use of masculine gender forms instead of feminine which is still widespread and often used feature not only in the deep Tamian subdialects, but also in the Kurzeme’s non-deep subdialects and Vidzeme’s Livonianized subdialects. Another typical and often used morphological peculiarity is the use of the 3rd person verb forms in all persons and numbers. Both features appear more rarely in the speech of the younger generation than in the speech of the middle and older generation, because younger people are avoid using those, introducing the standard language forms instead of the dialectal forms.As the gathered materials show, it is still possible to hear typical phonetic and morphological features in the researched deep Tamian subdialects, but as it is clear that these features have changed since the last century, when extensive dialectal researches on Latvian dialectology were made, it is particularly important to study the dynamics of dialect phenomena nowadays.
Keywords: phonetics; morphology; the deep Tamian (Tāmnieki) subdialects; the Livonianized dialect; nowadays